(untitled) (Journal of the College of Education for Women, 2019)
This research endeavors to clarify the relationship between the general policies of the country and Civil Organizations (Cos). This requires that we first identify the concepts of making polices on the one hand, and of COs on the other hand. Initially, polices starts as personal ideas that are, later, turned by some groups of people into suggestions. When the governments adopt these suggestions, they become state policies as shown by the following: Idea ———-> Suggestion——–> Policy. COs are groups of free voluntary organizations acting to bridge the gap between the state and the public, and to respond to the latter’s demands. The organizations includes, among others, trade unions and professional associations. In other words, they have something to do with all institutions that have no connections to government. This delimiting of the concepts allows us to show the nature of relationship that emerge between COs and the process of making policy. This relationship is not only changeable but it constantly changes and takes different forms and contents. This is due to the fact that COs exercise their impact on the process of making policy through various ways, among which are the mobilization of the public opinion, the effect they have on political parties, the provision of information, the support they render to election campaigns, protests, demonstrations and setting gatherings and the act of resorting to courts. Therefore, COs play an active role of drawing up governmental policies because of the direct and indirect means they have, means that exercise their impact on policies as well as on those executing these policies.